Government regulation number 92 of 2015 for the compensation for victims of the wrongful criminal justice process in Indonesia: an overview of implementation (2015-2024) - Rahmawati, Erni; Abdurakhman; Mulyatari, Dwi (Future Science, 2025)
The Wrongful Criminal Justice Process (WCJP) has been a persistent issue in Indonesia, with Government Regulation No. 92 of 2015 (PP RI 92/2015) enacted to enhance compensation mechanisms for its victims. This study critically examines the implementation of PP RI 92/2015 from its enactment in 2015 to 2024, aiming to provide a comprehensive overview of current victim compensation systems and, crucially, to identify the structural obstacles hindering its effective application. Adopting a qualitative approach, this research utilizes a structuralist historical methodology, analyzing data sourced from previous research, academic literature, and relevant legal regulations. The findings reveal a stark reality of limited implementation success: only one known case received compensation, and this was after a protracted six-year process. Significant structural impediments identified include a persistent lack of clarity in institutional responsibilities, the notable absence of technical implementation guidelines for PP 92/2015, issues stemming from the Ministry of Finance's role in payment procedures and budget allocation, and the stalled operationalization of the Ombudsman's potential role. This study offers a novel, in-depth historical analysis of PP RI 92/2015's decade-long implementation challenges, highlighting how underlying structural deficiencies, rather than mere technical flaws, contribute to the regulation's practical inefficacy in delivering timely and appropriate justice to WCJP victims.